(untitled) (Carte Romanze, 2025)
The paper adds a new witness to the tradition of two previously publisheed frottole from the fourteenth century. After providing a description of the manuscript, it proceeds to integrate the witness within the already examined tradition in order to update the stemma codicum and the critical apparatus.